Terapi Latihan, Infrared, Serta Transcutaneous Electrical Nerve Stimulation Pada Pasien Osteoarthritis Knee - Taufik Eko Susilo taufik; Rachmita Ramadhani rachmita (Publikasi Indonesia, 2022)
Osteoarthritis is a degenerative disease in the supply that involves cartilage, joint layers, ligaments, and bones so that it can cause pain and stiffness in the joints. Almost 70% of osteoarthritis is experienced by those over the age of 50 years characterized by the presence of structural damage in the joints. The purpose of this study is to control the pain felt by the patient and improve the functional ability of the daily activities carried out by the patient. This study included a case study conducted at one of the hospitals in the city of Sragen on a patient Mrs. SNR, aged 71 years, working as a housewife. The patient complains of pain in both knees, the patient also has difficulty performing squat movements to the stand, standing for a long time, rising from sitting to standing, difficulty in praying. This research method was carried out by therapeutic patients for 2 x / week in 3 weeks, one therapy followed for 30 minutes. Patients are given therapy in the form of exercise, infrared and tens therapy. Pain was measured using the Numeric Rating Scale (NRS) and Western Ontario and the McMaster Universities Arthritis Index (WOMAC) to measure patient functional activity. Conclusion: modalities given by physiotherapy such as Quadriceps Setting Exercises, Passive Stretching, infrared (IR) and Transcutaneous Electrical Nerve Stimulation (TENS) given as many as 4 meetings can increase daily functional activities and there is a decrease in pain.